On Quine on Arrow - Salles, Maurice (Springer, 2017)
This paper describes an unknown episode in the development of the theory of social choice. In the Summer 1949, while at RAND, Quine worked on Arrow's (im)possibility theorem. This work was eventually published as a paper on (applied) set theory totally disconnected from social choice. The working paper directly linked to Arrow's work was never published.